BTT-ECMO Trends and Outcomes Under Revised Heart Allocation System - Aniket S. Rali, MD, FACC, FCCP; Het Patel; Matthew M. Lander; Kaitlyn Brennan; John Trahanas; Kelly Schlendorf; JoAnn Lindenfeld; Manreet Kanwar (JHLT Open)
Under the revised UNOS heart allocation system, waitlist and post-transplant outcomes among patients bridged to transplant with VA-ECMO (BTT-ECMO) have improved. However, it remains largely unknown if these early trends have persisted over time. We queried the UNOS database for all adult heart-only BTT-ECMO recipients between January 2019 and December 2022. Our analysis shows that under the revised system, waitlist mortality and 1-year post-transplant outcomes have remained favorable, despite increased utilization of BTT-ECMO. This finding supports the original intent of the revised allocation system in ensuring more rapid transplantation of the sickest patients while avoiding a higher post-HT mortality.